Improved culture-based detection and quantification of Burkholderia pseudomallei from soil. - Trung, T; Hetzer, A; Topfstedt, E; Göhler, A; Limmathurotsakul, D; Wuthiekanun, V; Peacock, S; Steinmetz, I (2011)
Environmental surveillance of the Gram-negative soil bacterium Burkholderia pseudomallei, the aetiological agent of melioidosis, is important in order to define human populations and livestock at risk of acquiring the infection. This study aimed to develop a more sensitive method for the detection of B. pseudomallei from soil samples in endemic areas compared with the currently used culture method based on soil dispersion in water. We report the development of a new protocol that involves soil dispersion in a polyethylene glycol (PEG) and sodium deoxycholate (DOC) solution to increase the yield of viable B. pseudomallei from soil samples. Comparative testing of soil samples from Northeast Thailand covering a wide range of B. pseudomallei concentrations demonstrated a significantly higher recovery (P<0.0001) of B. pseudomallei colony-forming units by the new method compared with the conventional method. The data indicate that using the detergents PEG and DOC not only results in a higher recovery of viable B. pseudomallei but also results in a shift in the bacterial species recovered from soil samples. Future studies on the geographical distribution and population structure of B. pseudomallei in soil are likely to benefit from the new protocol described here.